A 6-day high-intensity interval microcycle improves indicators of endurance performance in elite cross-country skiers - Rønnestad, Bent R.; Bjerkrheim, Kjetil Andre; Hansen, Joar; Mølmen, Knut Sindre (Frontiers in Sports and Active Living, 2022)
Purpose: The aim of this study was to compare the effects of a 6-day high-intensity interval (HIT) block (BLOCK, n=12, maximal oxygen uptake (V̇O2max=69.6±4.3 mL∙min-1∙kg-1) with a time-matched period with usual training (CON, n=12, V̇O2max= 69.2±4.2 mL∙min-1∙kg-1) in well-trained cross-country (XC) skiers on physiological determinants and indicators of endurance performance. Furthermore, the study aimed to investigate the acute physiological responses, including time ≥90% of V̇O2max, and its associated reliability during repeated HIT sessions in the HIT microcycle. Methods: Before the 6-day HIT block and following 5 days of recovery after the HIT block, both groups were tested on indicators of endurance performance. To quantify time ≥90% of V̇O2max during interval sessions in the HIT block, V̇O2 measurements were performed on the 1st, 2nd, and last HIT session in BLOCK. Results: BLOCK had a larger improvement than CON in maximal 1-min velocity achieved during the V̇O2max test (3.1±3.1% vs. 1.2±1.6%, respectively) and velocity corresponding to 4 mmol∙L-1 blood lactate (3.2±2.9% vs. 0.6±2.1%, respectively). During submaximal exercise, BLOCK displayed a larger reduction in respiratory exchange ratio, blood lactate concentration, heart rate, and rate of perceived exertion (p<0.05), and a tendency towards less energy expenditure compared to CON (p=0.073). The ICC of time ≥90% V̇O2max in the present study was 0.57, which indicates moderate reliability. Conclusions: In well-trained XC skiers, BLOCK induced superior changes in indicators of endurance performance compared with CON, while time ≥90% of V̇O2max during the HIT sessions in the 6-day block had a moderate reliability.